LE RIPAE DI ROMA IN ETÀ IMPERIALE: QUALCHE EVIDENZA DALLA PIANTA MARMOREA SEVERIANA - Muzzioli, Maria Pia (Riparia, 2018)
Some tracts of the Tiber ripae in imperial period are depicted in many slabs of the Severan marble plan of Rome. The ripae, right and left, South of the great bridges, appear variously but systematically equiped to discharge goods coming from Portus, to store and distribute them. From the Insula Tiberina to the North the ripae, less documented by the marble fragments, are very differently equiped on the left (Campus Martius) than on the right (suburban area, with horti). The ripae delimitation by cippi further northwards and southwars the urban area prove that the delimitation was evidently functional in controlling the flow of the Tiber and the connected activities, not only the town planning.